Keterampilan membaca puisi siswa sebuah modifikasi teknik membaca puisi Jose Rizal Manua - Fauzi Afriansyah; Prima Gusti Yanti (Universitas Ahmad Dahlan, 2020)
This study aims to describe students' reading skills using a modification of Jose Rizal Manua's declamator technique in his book Reading Poetry. This research was conducted on students of Al Azhar 22 Middle Islamic Primary School. The method used is a qualitative method using modeling. The data source from this study came from five students who came from different classes but had an interest in poetry reading activities. The data in this study consisted of videos, sound recordings, and student notes collected by the teacher. In this study, poetry reading techniques at three stages of work, namely the work of the brain, work of the heart, and work of the body. Can be concluded about the use of modifications to this technique can improve students' poetry reading skills. The average value of the calculated value = 82 is greater than the value of the minimum graduation criteria = 75. Can be perfected by using a modification of Jose Rizal Manua's poetry reading technique can improve student skills in reading poetry.